"China's Ascension to Superpower Status: Examining the Impact on the Current Geopolitical Landscape and Global Power Dynamics" - Lorenca Bejko (International Journal of Integrative Sciences, 2024)
The climb of the dragon stirs waves across the wide sea. As gold and steel flow from its mountains, China's power shakes pillars of the old world. This writing aims to weigh what this means through windows into trade, trust, and talk between lands. By peering closely at ties tied in knots, may we grasp how the rise of the rising sun redraws the dance of nations. China has become a colossus with colossal clout on the global stage. As a financial, political, and military giant emerging from the east, its growing heft has brought challenges and chances to the structure that has stood for ages. This essay will think on these effects by glancing at China from angles of economics, exchange, security, and diplomacy. When we pick at threads in this knotty matter piece by piece, it is hoped this essay helps us understand better how the ascent of this dragon recasts the play of peoples across the planet